PENGARUH DISIPLIN KERJA, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ( Studi Pada Badan Kepegawaian Daerah Provinsi Jawa Tengah ) - Dahliatul Mujtahidah, 14.05.51.0050; Waru wu, Penunjang (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the influence of work discipline , training, and work environment on the employees performance of Badan Kepegawaian Daerah Provinsi Jawa Tengah. Respondents research it consists of 93 on officials of Badan Kepegawaian Daerah Provinsi Jawa Tengah. Model analysis the data used was test validity with product moment, reliability testing with Cronbach Alpha and multiple linear regression as using software IBM SPSS version 20,0 to examine and prove a hypothesis research. The data collected following the completion of testing the results all data expressed valid and reliable. The result of analysis and discussion shows that: (1). Work dicipline It has some positive effects and significant impact on the employees performance, (2). Training have had a positive effect and significant of the performance of employees, and (3). Work environment have had a positive effect and insignificant of the performance of employees. Simultaneously discipline work , training , and work environment influential positive and significant of the employees performance.Keyword : Work Dicipline, Training, Work environment, Employees performance